A method based on the granger causality and graph kernels for discriminating resting state from attentional task - Danesh Shahnazian; Fatemeh, Mokhtari; Hossein-Zadeh, Gholam-Ali (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/